Particulate plastics in terrestrial and aquatic environments - Bolan, Nanthi S.; Kirkham, M. B.; Halsband, Claudia; Nugegoda, Dayanthi; Ok, Yŏng-sik (New York: CRC Press, 2020)
"Particulate Plastics in Terrestrial and Aquatic Environments provides a fundamental understanding of the sources of these plastics and the threats they pose to the environment. It demonstrates the ecotoxicity of particulate plastics using case studies and offers management practices to mitigate environmental contamination"--
Sources of particulate plastics in terrestrial ecosystems -- Particulate plastics from agriculture -- Polyacrylamide (PAM) as a source of particulate plastics in terrestrial environment -- Analytical methods for particulate plastics in soil and water -- Chemistry and processing of plastics -- Particulate plastics and natural organic matter interactions -- Characteristics of particulate plastics in terrestrial ecosystems -- Facilitated transport of particulate plastics through soil macropores as a mechanism for groundwater contamination -- Microbial plastisphere: Microbial habitation of particulate plastics in terrestrial and aquatic environments -- Aggregation behavior of particulate plastics and its implications -- Environmentally toxic components of plastic manufacture -- Particulate plastics as vectors of heavy metal(loid)s -- Water relations and cadmium uptake of wheat grown in soil with particulate plastics -- Particulate plastics as vectors of organic pollutants -- Ecological impacts of particulate plastics in marine ecosystems -- Sublethal responses to microplastic ingestion in invertebrates : towards a mechanistic understanding using energy flux -- Particulate plastics and human health -- Status of particulate marine plastics in Sri Lanka -- Case studies of particulate plastics distribution and ecotoxicity : Japan -- Particulate plastics distribution and ecotoxicity in marine ecosystems in Thailand and Southeast Asia -- The current status of plastics : a New Zealand Perspective -- Plastic food for fledgling short-tailed shearwaters (Ardenna tenuirostris) : an Australian case study -- Management of particulate plastics -- Management of particulate plastic waste input to terrestrial and aquatic environment -- Evaluation and mitigation of the environmental impact of synthetic microfibers -- Bioplastics : a silver bullet to plastic pollution?
Keywords: Microplastics; Pollution prevention